NGHIÊN CỨU TỔNG HỢP LISINOPRIL DIHYDRATE TỪ CHẤT TRUNG GIAN CHÌA KHÓA N2-[1(S)-ETHOXYCARBONYL-3-PHENYLPROPYL]-N6-TRIFLUOROACETYL-L-LYSINE - Quốc Vượng, Nguyễn; Văn Chiến, Vũ; Thị Thu, Nguyễn; Thị Huế, Nguyễn; Tiến Đạt, Nguyễn; Văn Cường, Phạm; Văn Minh, Châu (Vietnam Journal of Science and Technology, 2017)
Lisinopril dihydrate was synthesized from the key intermediate N2-[1(S)-ethoxycarbonyl-3-phenyl propyl]-N6-trifluoroacetyl-L-Lysin (li5). This intermediate was activated to form cyclic N-anhydride compound li6 by using N,N-carbonyldiimidazole, subsequently, the coupling reaction of li6 with L-proline methyl ester (li3) to give fully protected lisinopril derivative li7 in high yield. The last step is the deprotection of li7 via hydrolysis using aqueous solution 1N NaOH in methanol to obtain lisinopril. The crude lisinopril was recrystalized from solvent system isopropanol/H2O(10/1; v/v ml) afforded lisinopril dihydrate li8. The structure of the obtained compounds have been confirmed by IR, ESI-MS, 1H, 13C-NMR, COSY, HMBC, HSQC spectra, and [a]D suitable with literatures; The purity of obtained lisinopril li8 was identified by HPLC method and H2O content was determined by Karl Fischer Titration.